2020
DOI: 10.1029/2019gl086773
|View full text |Cite
|
Sign up to set email alerts
|

Broad Consistency Between Observed and Simulated Trends in Sea Surface Temperature Patterns

Abstract: Using seven single-model ensembles and the two multimodel ensembles CMIP5 and CMIP6, we show that observed and simulated trends in sea surface temperature (SST) patterns are globally consistent when accounting for internal variability. Some individual ensemble members simulate trends in large-scale SST patterns that closely resemble the observed ones. Observed regional trends that lie at the outer edge of the models' internal variability range allow two nonexclusive interpretations: (a) Observed trends are unu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 82 publications
3
41
0
Order By: Relevance
“…For reference, trends in the equatorial Pacific SST gradient (discussed below) are about an order of magnitude larger. Thus, errors in the trends of Δ conv and SST # in the observational record may be possible even if the large-scale spatial patterns of SST trends are, as argued by Olonscheck et al (2020) for the ERSSTv2, COBE2 and HadISST2 SST reconstructions, broadly consistent with the range covered by internal variability of coupled atmosphere-ocean GCMs. The verification of trends in Δ conv from observations independent of SSTs is difficult.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For reference, trends in the equatorial Pacific SST gradient (discussed below) are about an order of magnitude larger. Thus, errors in the trends of Δ conv and SST # in the observational record may be possible even if the large-scale spatial patterns of SST trends are, as argued by Olonscheck et al (2020) for the ERSSTv2, COBE2 and HadISST2 SST reconstructions, broadly consistent with the range covered by internal variability of coupled atmosphere-ocean GCMs. The verification of trends in Δ conv from observations independent of SSTs is difficult.…”
Section: Discussionmentioning
confidence: 92%
“…The question whether the trend in the equatorial Pacific East‐West SST gradient seen in the observational SST reconstructions over recent decades is consistent with results from coupled atmosphere‐ocean GCMs has in itself received much attention (e.g. Coats & Karnauskas, 2017; Olonscheck et al., 2020; Watanabe et al., 2021). The recent analysis by Watanabe et al.…”
Section: Discussionmentioning
confidence: 95%
“…By combining the GCM, RCM, and nat-GCM SMILEs we can further investigate the response of both SAT and precipitation to large volcanic eruptions over Europe. To investigate the response to volcanoes previous studies have shown that many ensemble members are needed to tease out the forced response (Maher et al, 2015;Pausata et al, 2015;Bittner et al, 2016;Milinski et al, 2020), meaning that SMILEs are an ideal tool to investigate this question.…”
Section: Attributing Climate Responses To Volcanic Eruptionsmentioning
confidence: 99%
“…In sum, we argue that the El Niño‐like SST change pattern constitutes a factor that should be taken into account in examining the jet extension. However, as there is a large spread in the El Niño versus La Niña‐like SST warming pattern over the tropical Pacific among the CMIP5 coupled climate models (e.g., Li et al., 2016; Olonscheck et al., 2020; Seager et al., 2019), the effect of SST change pattern contributes to the large inter‐model spread in the jet extension and total precipitation change over California under global warming projected by the coupled models.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the SST change with El Niño‐like warming pattern has a secondary but also positive contribution to the jet extension via the tropical teleconnection to the North Pacific. However, this effect has a large spread among the CMIP5 coupled models as there is uncertainty in the tropical SST warming pattern between El Niño‐versus La Niña‐like warming over the tropical Pacific (e.g., Li et al., 2016; Olonscheck et al., 2020; Seager et al., 2019). Relative to the SST forcing, the direct CO 2 radiative forcing on the wetting California is negligible.…”
Section: Conclusion and Discussionmentioning
confidence: 99%